2021
DOI: 10.1016/j.jshs.2020.02.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acute aerobic exercise on central arterial stiffness, wave reflections, and hemodynamics in adults with diabetes: A randomized cross-over design

Abstract: Highlights This is the first study examining the effect of acute aerobic exercise on central arterial stiffness, wave reflections, and hemodynamics in people with diabetes. A significant group × time interaction was found for changes in central systolic blood pressure and augmentation index at a heart rate of 75 bpm. A reduction in central systolic blood pressure was observed following high-intensity interval exercise; no changes were found after moderate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 32 publications
(55 reference statements)
2
18
0
Order By: Relevance
“…We thank Lopes et al 1 for their interest in our study and for writing an insightful commentary based on our findings, which were recently published in the Journal of Sport and Health Science , 2 and for their work. 3 As noted by the authors, there is consistency in several key findings between our laboratories, and this should serve as a basis for future investigation in this area.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…We thank Lopes et al 1 for their interest in our study and for writing an insightful commentary based on our findings, which were recently published in the Journal of Sport and Health Science , 2 and for their work. 3 As noted by the authors, there is consistency in several key findings between our laboratories, and this should serve as a basis for future investigation in this area.…”
mentioning
confidence: 85%
“…Previous work examining the effect of aerobic exercise in both acute and chronic exercise settings on such arterial health outcomes has been conducted predominately in young, healthy adults. 4 As highlighted in the commentary by Lopes et al, 1 a transient reduction in wave reflections (as measured by augmentation index at a heart rate of 75 beats/min (AIx@75)) may be intensity dependent, given the findings from each of our respective studies in adults with diabetes 2 or obesity. 3 Both studies observed a significant transient reduction in AIx@75 following a single bout of HIIE; this did not occur after a single bout of moderate-intensity continuous exercise (MICE) or control.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…We read with great interest the study by Way et al 1 published in this journal, which described and compared the acute changes in central arterial stiffness (AS), wave reflections, and central hemodynamics (CH) in response to a bout of high-intensity interval exercise (HIIE) and moderate-intensity continuous exercise (MICE) in adults with diabetes. The authors reported a significant reduction in augmentation index (AIx) corrected by a heart rate (HR) of 75 beats/min (AIx@75) and central systolic blood pressure after HIIE, without significant changes in the pulse wave velocity (PWV).…”
mentioning
confidence: 99%
“…1 B). The acute nature of the exercise seems to be insufficient stimulus to alter the structural proprieties of the arteries, such as elastin breakdown and collagen deposition in the media layers, 16 which might justify the absence of change in PWV following AE observed by Way et al 1
Fig 1 HIIE, MICE, and control condition protocols (A) of the acute bout of HIIE and MICE on cfPWV (B), AIx (D), and AIx@75 (F), and 8 weeks of HIIE and MICE on cfPWV (C), AIx (E), and AIx@75 (G) in young obese women. * Differences in relation to baseline values.
…”
mentioning
confidence: 99%